Factors Influencing Consumer Purchase Intentions: A Study of E- Commerce Platforms in South Africa - Tsotesi, Nolo (University of the Witwatersrand, Johannesburg, 2023)
The purpose of this study is to examine the effects of a set of determinants on the purchase intention of consumers using an electronic commerce (online shopping) platform in the South African context. Since the beginning of the COVID-19 pandemic, there has been high demand for online activities in South Africa and retailers have had to turn to online platforms to start or continue serving their customers. In turn, customers turned to online platforms to find and purchase goods and services. This has fast-tracked digitisation for many retailers and sellers, forcing a digital culture despite the level of preparedness for this new way of living. As such, this has encouraged existing and new online stores to enhance their online appearance and services to promote consumer activity and sales
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Electronic-Commerce (E-Commerce); Online Shopping Platforms; Mobile-Commerce (M-Commerce); Online Retail; Online Shopping Behavior; Consumer Purchase Intentions; South Africa; Utilitarian Value; Hedonic Value; UCTD; SDG-8: Decent work and economic growth